Results from PSIPROSPER: A multicenter retrospective study to analyze the impact of treatment with paliperidone palmitate 1-month on clinical outcomes and hospital resource utilization in adult patients with schizophrenia in Portugal - Marques-Teixeira, João; Amorim, Gonçalo; Pires, Ana Catarina (Frontiers in Psychiatry, 2022)
Background Schizophrenia is a chronic psychiatric disorder with a significant impact worldwide. The early onset and its relapsing nature pose a significant challenge to patients and caregivers. The PSIPROSPER study aimed to characterize the real-world context of schizophrenia treatment in Portugal and to measure the impact of including paliperidone palmitate 1-month formulation (PP1M) in the clinical outcomes (relapses and hospitalizations) and healthcare resource utilization, in a context in which payment scheme in Portugal allows for patients to receive free antipsychotics if prescribed at public hospitals. Methods This was a multicenter, retrospective, observational study. Male and female adults with a diagnosis of schizophrenia who initiated treatment with PP1M after a minimum of 12 months on an Oral Antipsychotic (OAP), and with complete medical charts, were consecutively included. A mirror-image design over 24 months allowed the comparison of outcomes before and after the PP1M introduction. Results Out of the 51 patients included, 80.4% were male, with a mean age of 34 (±9.8) years. Around 92% of patients were being treated with PP1M at inclusion. Lack of adherence to previous OAP was the main driver for PP1M initiation. Only 9.8% of patients were hospitalized during the PP1M period vs. 64.7% during the OAP period (p < 0.0001). The mean number of hospitalizations (0.1) was significantly lower during the PP1M period (p < 0.0001). Type of treatment was the only variable found to be significant in predicting a lower hospitalization rate and a lower risk of hospitalization. Relapses were significantly lower (p < 0.0001) in PP1M (21.6%) vs. OAP (83.7%). Similarly, the mean change in the number of relapses (p < 0.0001) showed significantly better outcomes in PP1M. Conclusion This study supports PP1M as part of schizophrenia treatment in Portugal. Given the lower number of relapses and hospitalizations observed in schizophrenia patients treated with PP1M when compared to OAP-treated patients, this real-world study seems to provide further evidence to support the use of PP1M to treat this condition, in line with previous research. In the context of scarce public resources, these benefits should be carefully considered by healthcare decision-makers to ensure optimal value-based treatment strategies.